PERSPEKTIF PHYLOGENESIS DAN ONTOGENESIS DALAM PENGEMBANGAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN ASPEK SEJARAH MATEMATIKA - Shofan Fiangga; Abdul Haris Rosyidi; Tatag Yuli Eko Siswono (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
History of mathematics discusses a historical aspect of mathematics concepts since its appearance and development through ages. Understanding the background of why a certain concept appears in mathematics, an innovation in teaching and learning material may be developed. The historical aspect of mathematics concept can be used as guided reinvention activities for the children to learn the concept. This idea is in line with what stated in curriculum 2013. However, to implement in curriculum 2013, there is no feasible framework that can be used to work on. One perspective that can be used in this implementation is phylogenensis and ontogenesis perspective. In this paper a discussion on how phylogenesis and ontogenesis may be used to implement the history in teaching mathematics will be presented. In addition, an example on how a history can be used as reference in learning is provided.